Extensive HPV-Related Carcinoma In Situ of the Upper Aerodigestive Tract with ‘Nonkeratinizing’ Histologic Features - Chernock, Rebecca D. (Springer US, 2013)
Over the past several decades, it has become clear that human papillomavirus (HPV) is important for the development and progression of many head and neck squamous cell carcinomas, particularly those arising in the oropharyngeal tonsillar crypts. Yet, our understanding of HPV’s role in premalignant squamous lesions remains relatively poor. This is in part because premalignant lesions of the oropharyngeal tonsillar crypt tissue, where most HPV-related carcinomas arise, are difficult if not impossible to identify. Recent evidence does suggest a role for HPV in a subset of premalignant lesions of the surface epithelium, especially the oral cavity, despite the rarity of HPV-related invasive squamous cell carcinomas at this site. Furthermore, these HPV-related oral cavity dysplasias appear to have unique, bowenoid histologic features described as ‘basaloid’ with full-thickness loss of squamous maturation, mitotic figures and apoptosis throughout. Here, we present a unique case of an HPV-related premalignant lesion (squamous cell carcinoma in situ) extensively involving the surface epithelium of the oral cavity, oropharynx and larynx that had ‘nonkeratinizing’ histologic features typical of HPV-related invasive squamous cell carcinoma. This case was strongly p16 positive by immunohistochemistry and harbored transcriptionally active HPV as demonstrated by E6/E7 RNA in situ hybridization. Furthermore, the patient had an excellent response to radiation treatment.